How subprime borrowers and mortgage brokers shared the pie - Antje Berndt; Burton Hollifield; Patrik Sandås (Sveriges Riksbank, 2014)
We develop an equilibrium model for origination fees charged by mortgage brokers and show how the equilibrium fee distribution depends on borrowers' valuation for their loans and their information about fees. We use non-crossing quantile regressions and data from a large subprime lender to estimate conditional fee distributions. Given the fee distribution, we identify the distributions of borrower valuations and informedness. The level of informedness is higher for larger loans and in better educated neighborhoods. We quantify the fraction of the surplus from the mortgage that goes to the broker, and how it decreases as the borrower becomes more informed.
Keywords: G21; 330; Mortgage broker compensation; Borrower Valuation; Borrower Informedness